234k views
2 votes
The sum of the roots of x^2+6x-55=0

User Nybbler
by
4.4k points

2 Answers

1 vote

Answer:

The sum is -6

User Janna
by
4.3k points
3 votes

Answer:

The sum of the roots is
-6

Explanation:

we know that

The formula to solve a quadratic equation of the form
ax^(2) +bx+c=0 is equal to


x=\frac{-b(+/-)\sqrt{b^(2)-4ac}} {2a}

in this problem we have


x^(2) +6x-55=0

so


a=1\\b=6\\c=-55

substitute in the formula


x=\frac{-6(+/-)\sqrt{6^(2)-4(1)(-55)}} {2(1)}


x=\frac{-6(+/-)√(256)} {2}


x=\frac{-6(+/-)16} {2}


x1=\frac{-6(+)16} {2}=5


x2=\frac{-6(-)16} {2}=-11

The roots are
5,-11

Find the sum of the roots


5+(-11)=-6

User Proseosoc
by
5.5k points